Imagining the data economy - Lehtiniemi, Tuukka (fi=Turun yliopisto|en=University of Turku|, 2020)
The digital environment is increasingly organised to transform aspects of people’s lives into data in order to make use of those data in the production of economic value. Data activism has emerged as one response to the resulting asymmetries in data usage and distribution. Adopting the concept of collective imagination, this thesis investigates imaginaries about an alternative data economy developed in data activism. Based on the data studies literature, a view of the dominant data economy imaginary is first constructed. It consists of collectively shared notions about how the data economy currently functions and ought to function. Based on four original publications, alternative imaginaries are compared with the dominant imaginary. The aim is to examine the alternative imaginaries and their underpinnings and to scrutinize the desirability of the data futures they promote. Empirical research in this thesis has focused on MyData, a data governance initiative striving for a more central role for people in the data economy. The thesis identifies two alternative imaginaries developed in the context of the initiative: the market imaginary and the citizen imaginary. Both build on the notion of data agency, that is, providing people with new capabilities to act in relation to personal data. The market imaginary is based on viewing data agency as market choice, and relies on the market for data governance. Individuals are imagined to act in data markets to improve their lives, making data serve their personal ends. The citizen imaginary foregrounds collective data governance and the common good. Here, data agency is imagined as citizens’ collective capability to participate in the processes that determine how and for what purposes their data are used. This thesis discusses how the market imaginary is the better positioned of the two to expand beyond data activism; it resonates with notions about technology as the enabler of individual choice, leverages existing regulatory instruments, and is aligned with commercial views of the value of data. Based on this research, however, the reliance on market agency appears as a precarious starting point for a desirable data future. The practical implication is to encourage data activists to experiment on collective data governance and on new ways to make data valuable alongside the market-oriented ones. The implication for data activism research is that identifying imaginaries underpinning activist initiatives can aid with shaping pathways toward a desirable digital environment.

Digitaalisessa ympäristössä̈ ihmisten elämästä tuotetaan dataa tavoitteena taloudellisen arvon luominen. Data-aktivismi on yksi reaktio datan käytön ja jakautumisen epäsymmetrioihin. Tässä työssä tarkastellaan kollektiivisen mielikuvituksen käsitteen avulla data-aktivismissa tuotettuja vaihtoehtoisia datatalouden mielikuvastoja, imaginaareja. Sosiaalitieteellisen datatutkimuksen avulla rakennetaan näkymä dominoivaan datatalouden imaginaariin. Tätä verrataan neljään tutkimusjulkaisuun pohjautuen data-aktivismissa tuotettuihin vaihtoehtoisiin datatalouden imaginaareihin. Tavoitteena on paitsi eritellä vaihtoehtoisia imaginaareja, myös tarkastella niiden edistämien tulevaisuuden datatalouden muotojen tavoiteltavuutta. Väitöskirjan empiirisenä tutkimuskohteena on MyData, datan hallintaa koskeva aloite, joka pyrkii muovaamaan ihmisille keskeisemmän rooliin tulevaisuuden datataloudessa. Tutkimuksen perusteella aloitteessa vaikuttaa kaksi datatalouden imaginaaria, jotka ovat sekä toisilleen että dominoivalle imaginaarille vaihtoehtoisia. Molemmat nojaavat ajatukseen ihmisten lisääntyvästä toimijuudesta suhteessa heitä koskevaan dataan. Markkinaimaginaari nojaa markkinoihin datan hallintamekanismina. Tällöin toimijuus kiteytyy valintoihin markkinoilla: ihmisten ajatellaan tekevän valintoja, joissa data palvelee heidän henkilökohtaista etuaan. Kansalaisimaginaari nojaa ajatukseen kollektiivisesta datan hallinnasta ja datasta saatavista yhteisistä hyödyistä. Toimijuus datan suhteen kytkeytyy tällöin kollektiivisiin prosesseihin, jotka ohjaavat datan käyttöä ja käytön päämääriä. Tutkimuksen perusteella markkinaimaginaarilla on näistä kahdesta paremmat edellytykset laajentua data-aktivismin ulkopuolelle: se hyödyntää olemassa olevaa sääntelyä, pohjautuu vakiintuneisiin käsityksiin datan taloudellisesta arvosta ja korostaa yksilön valinnanvapautta tukevaa teknologiaa. Tutkimuksen valossa luottaminen markkinatoimijuuteen yksinään vaikuttaa epävarmalta pohjalta tulevaisuuden datataloudelle. Työn käytännön implikaatio on rohkaista data-aktivismia kehittämään kollektiivisia datan hallinnan tapoja ja arvonmuodostuksen muotoja markkinavalinnan ohella. Työn implikaatio data-aktivismin tutkimukselle on osoittaa, että data-aktivismin taustalla vaikuttavien imaginaarien tunnistaminen auttaa kartoittamaan toivottavaa tulevaisuuden digitaalista ympäristöä.